Doença hepática gordurosa não alcoólica em pacientes com psoríase - Simal, Thaiza Alonso [UNIFESP] (2017)
Introduction: The prevalence rates of nonalcoholic fatty liver disease is increased in psoriasis and vary depending of the region studied. The factors associated with nonalcoholic fatty liver disease in psoriasis, as well as the severity of liver disease in this population, are not fully understood. Objectives: Evaluation of the prevalence of nonalcoholic fatty liver disease in patients with psoriasis, the different degrees of liver fibrosis in patients with liver disease and the comparison of epidemiological, clinical and laboratory characteristics between psoriasis patients with and without nonalcoholic fatty liver disease. Methods: Patients with psoriasis followed up at a Dermatology Service of Unifesp between 2015 and 2016 and submitted to abdominal ultrasound were enrolled. Clinical-epidemiological and laboratory characteristics were compared between patients with and without steatosis. Liver fibrosis was evaluated by transient hepatic elastography. The results were analyzed using the chi-squared or Fisher’s exact test when appropriate, Student t-test or Mann-Whitney and logistic regression analysis. Results: One hundred and seventy-one patients with a mean age of 50 years and with a slight predominance of men (52%) were studied. The prevalence of nonalcoholic fatty liver disease was 51%. Patients with psoriasis and nonalcoholic fatty liver disease had a higher body mass index (p = 0,036), higher prevalence of metabolic syndrome (p < 0,001), more severe psoriasis area severity index (p = 0,005) and higher alanine aminotransferase serum levels (p = 0,002). Transient elastography was performed on 52 patients with nonalcoholic fatty liver disease and detected significant fibrosis in 36% of cases, including cirrhosis in 15%. Conclusion: The high prevalence of liver disease in psoriasis and its association with metabolic syndrome and severe psoriasis area severity index suggest a common physiopathogenic factor for these diseases. The presence of a significant number of patients with advanced liver disease alerts to the need for systematic evaluation of this condition among patients with psoriasis.